Bacterial resistance: A narrative review on Staphylococcus aureus, Klebsiella pneumoniae and Pseudomonas aeruginosa - Faria, Tatiana Mayra Rocha (2023)
The aim of this article is to present a narrative review of the bacteria Staphylococcus aureus, Klebsiella pneumoniae and Pseudomonas aeruginosa, addressing their resistance mechanisms, peculiarities and characteristics. Bacterial resistance has become a public health issue of worldwide relevance. Due to the misuse of antibiotics or even their prolonged use, many species of bacteria have become increasingly resistant to antimicrobial agents. The nosocomial environment, especially intensive care units, where patients undergoing treatment use antibiotics for prolonged periods of time, is the environment in which the emergence of these bacteria is most commonly detected, including Staphylococcus aureus, Klebsiella pneumoniae and Pseudomonas aeruginosa. Many actions have been taken by the governments of various countries, the pharmaceutical industry, international organizations and researchers, both to raise awareness about the correct use of antimicrobials and in the search for new molecules to combat these pathogens. Given the relevance of the subject, this study will present a narrative review of the mechanisms of resistance of the bacteria S. aureus, K. pneumoniae and P. aeruginosa, strains that are highly resistant to available antimicrobials, in an attempt to understand the role of these pathogens.